Thermal analysis and tribological investigation on TPU and NBR elastomers applied to sealing applications. (November 2018) - Pinedo, B.; Hadfield, M.; Tzanakis, I.; Conte, M.; Anand, M.
Abstract: This study investigates the contact temperatures reached due to frictional heating on TPU (Thermoplastic polyurethane) and NBR (Nitrile butadiene rubber) seal surfaces during operation. These elastomers present limited thermal resistance so an excessive temperature rise may affect their tribological performance. Sliding tests of the elastomers against steel cylinders were carried out and the surface temperature evolution was acquired during the tests using a high precision infrared camera. Frictional behaviour and temperature curves were analyzed. The influence of the experimental parameters, such as the sealing material, sliding velocity, applied load and steel surface conditions was examined. Experimental thermal results were compared with those calculated through well-established analytical models, in order to determine the advantages and limitations of the latter. Highligths: An experimental investigation on the frictional heating on seals has been carried out. Temperatures reached at the contact were measured through an infrared camera. Effect of surface finishing on the temperature rise was also studied. Experimental thermal results were compared with those calculated analytically. It was demonstrated that TPU and NBR elastomers present very different energy dissipation ways.